(untitled) (Fiep Bulletin - online, 2015)
The work that I wish to present to you this paper was carried out, first by with the aim of studying the dentist’s standing work posture As the work progressed, we became aware that all the peculiarities of this special posture were to be found in any other profession provided the latter was exercised in the standing position, with a frontal field of work.